MINAT WIRAUSAHA MAHASISWA FAKULTAS EKONOMI UNSWAGATI CIREBON - Prilovia, Henawati; Iskandar, Iskandar (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The aim of this research was to know: (1) the influence of both Entrepreneurship knowledge and family environment for interest in entrepreneurship students; and (2) the difference of entrepreneurship interest in the students who come from entrepreneurial families and non-entrepreneurial families.This research belongs to survey research. The population of this research was 989 students of economics faculty in Unswagati and the sample of this research was the 91 respondents among them. The data of this research were obtained through questionnaires. Multiple linear regression technique and independent samples t-test were employed as the data analysis technique. The result shows that: (1) There is a positive effect of entrepreneurship knowledge for entrepreneurial interest; (2) There is a positive effect of family environment for entrepreneurial interest; and (3) there are difference of entrepreneurial interest in the students of the Faculty of Economics who come from entrepreneurial families and non-entrepreneurial families.Â Keywords: Entrepreneurial interest, Entrepreneurship Knowledge, Family Environment.